Pengaruh Literasi Keuangan Syariah dan Kemudahan terhadap Minat Penggunaan Uang Elektronik DANA sebagai Alat Transaksi - Febrima Ayuningrum; Siti Sadiyah (STEBI Global Mulia Cikarang, 2022)
The development of information technology is increasing along with the times. The development of information technology can encourage digital economic growth because it will be more effective and efficient in terms of time. One form of implementation between technology and information with digital economic growth is the payment of non-cash transactions. This study aims to find out how the effect of ease of Islamic financial literacy on students' interest in using DANA electronic money as a transaction tool, to find out how convenience influences interest in using DANA electronic money as a transaction tool. And to find out how the influence of Islamic financial literacy and convenience simultaneously on the interest in using DANA electronic money as a transaction tool. In this study, researchers used the theory of financial literacy according to the OECD (2013) to build Islamic financial literacy requires knowledge, skills, attitudes and beliefs. The convenience theory according to Jogiyanto (2015) is that several indicators are easy to learn, controllable, clear and understandable, flexible, easy to master and use. The theory of interest according to Muklish Muhammad nur Zulfahmi (2018) there are three indicators that can be used to encourage interest, namely, encouragement within the individual, social motives and emotional factors. This study uses a quantitative approach and primary data. The population in this study were 112 students of STEBI Global Mulia Cikarang Islamic Economics Study Program with ages 19 to 35 years. The sample in this study was taken from the population using the slovin formula, so there were 88 respondents. The results of this study partially show that Islamic financial literacy has a significant effect on students' interest in using DANA electronic money as a transaction tool, because the t-value is 6.372 > the t-table value is 1.988 with sig 0.001 <0.05. Convenience has a significant effect on students' interest in using DANA as a transaction tool, because the t-value is 8.766 > the t-table value is 1.988 with sig 0.001 <0.05. Whereas Islamic financial literacy and convenience simultaneously have a significant effect on students' interest in using DANA electronic money as a transaction tool, because the calculated F value is 238.377 > table F value of 3.10 with sig 0.001 > 0.05.